2021
DOI: 10.1186/s12879-021-06291-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Geenius HIV-1/2 Confirmatory Assay for the confirmatory and differential diagnosis of HIV-1/HIV-2 in Japan and reliability of the Geenius Reader in the diagnosis of HIV-2

Abstract: Background NEW LAV BLOT I and II (LAV I and LAV II), they were only option for human immunodeficiency virus (HIV) confirmatory test, following HIV screening test using HIV Ag/Ab combination test in Japan. We evaluated the performance of Geenius HIV-1/2 Confirmatory Assay (Geenius), both as a confirmatory test and for differentiation between HIV-1 and HIV-2, in comparison with LAV I and LAV II. Methods Eighty-nine HIV-1-positive plasma specimens, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…On the opposite, assays designed only to identify HIV-2 infection, HIV-2 Blot 1.2 and New Lav Blot II, exhibited high rates of undetermined results and misclassified as HIV-2 some HIV-1 only infections (7% and 5%, respectively), a consequence of cross-reactivity between HIV-1 antibodies and HIV-2 proteins. These results are consistent with previous studies regarding HIV-1 infection sensitivities and undetermined results for INNO-LIA (27,36,37), HIV Blot 2.2 (36,38), New Lav Blot I and II (39,40) and Geenius (27, 36-39, 41, 42), summarized in Fig. 1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the opposite, assays designed only to identify HIV-2 infection, HIV-2 Blot 1.2 and New Lav Blot II, exhibited high rates of undetermined results and misclassified as HIV-2 some HIV-1 only infections (7% and 5%, respectively), a consequence of cross-reactivity between HIV-1 antibodies and HIV-2 proteins. These results are consistent with previous studies regarding HIV-1 infection sensitivities and undetermined results for INNO-LIA (27,36,37), HIV Blot 2.2 (36,38), New Lav Blot I and II (39,40) and Geenius (27, 36-39, 41, 42), summarized in Fig. 1.…”
Section: Discussionsupporting
confidence: 93%
“…New Lav Blot II and HIV-2 Blot 1.2 had reported sensitivities of at least 95% (32,43). INNO-LIA had a reported sensitivity of 100% (36,37), while sensitivity ranged from 85% to 100% for Geenius (27,(39)(40)(41)(42)44). However, most of these studies included a very limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Livant et al reported that two of 16 pre-seroconverted specimens that were HIV-1 RNA-positive were also HIV-2 gp140-reactive [ 11 ]. In our previous study, four of 89 (4.5 %) HIV-positive samples cross-reacted with the HIV-2 gp140 line, although all were identified as HIV-1-positive when analyzed using Geenius Reader [ 13 ]. Thus, HIV-2 gp140-reactive cases could be related to the cross-reactivity of anti-HIV-1 Abs or nonspecific reactions.…”
Section: Discussionmentioning
confidence: 99%